Estimating Ex Post Impacts and Rates of Return to International Agricultural Research for Development - Stevenson, James R.; Johnson, N.; Macours, K. (2018)
How to reconcile the challenges of rigorously assessing the impacts of international agricultural research on development outcomes with the well-documented and widely-cited high estimates of rates of return to investment in agricultural research? This question was raised during the SPIA session at ISPC17 (https://cas.cgiar.org/isdc/events/ispc-17-meeting) and this note provides an initial response. It first summarizes updated estimates of rates of return to agricultural research, funded in part by SPIA, but then describes key challenges to applying rates of return to estimate ex post impacts of research investments and identifies key elements of an alternative approach to thinking about and measuring the impacts of CGIAR research.